Evaluation of two techniques of pericardiostomy for the management of pericarditis in cattle - Manjunatha, D.R.; Suresh Kumar, R.V.; Shivakumar, V.; Veena, P.; Priyanka, N.; Vilas, D.; Balappanavar, B.R.; Nagaraju, N. (Indian Journal of Veterinary Surgery, 2026)
Twelve cases of cattle presented to the Veterinary College Hospital, Hassan, over a period of five years with the history of pyrexia, decreased milk yield, coughing, recurrent bloat and dyspnea were used in the study. Upon clinical examination it was observed that all the cattle were showing jugular pulsation, and brisket and submandibular oedema. These cattle were subjected to haematological, biochemical, ultrasonographic, radiographic and electrocardiographic evaluation. Based on the findings all the cases were diagnosed as those of pericarditis. These cases were randomly divided into two groups of six animals each and subjected for ultrasound aided pericardiostomy using Foley’s catheter No. 18 with the help of artificial inseminating gun as stylet and a 28 FG trocar catheter under local analgesia in standing position. The catheter was fixed to the skin and kept in position for 7-10 days. In serous or purulent pericarditis cases Foley’s catheter was employed for pericardiostomy technique to drain the pericardial fluid, however, in cases with fibrinous pericarditis 28 FG trocar catheter was found to be more helpful to drain the pericardial fluid.